Pendidikan Kristiani Transformatif: Kritik Terhadap Kurikulum Katekisasi Gereja Berdasarkan Filsafat Pedagogi Paulo Freire - Justice Zeni Zari Panggabean (Sekolah Tinggi Teologi Intheos Surakarta, 2022)
Abstract. This article aims to show the importance of Christian education in the church context which focuses on the history of faith and its relation to social discourse. In general, the practice of Christian education in the church is still indoctrinating. Highlighting this, this paper attempted to establish a dialogue between the theory of critical pedagogy (liberation) of Paulo Freire's thought and the Christian education of the church (sidi catechism). The discussion in this article shows that the application of Paulo Freire's concept of critical pedagogy can emancipate catechism learning as an experience of religious faith. The faith’s evidence is shown in the reflection of personal life and to the world around it. Transformative Christian education in the teaching of catechism is important to be carried out with critical action and reflection as an appreciation of living together for better social change.Abstrak. Artikel ini bertujuan untuk menunjukkan pentingnya Pendidikan Kristiani dalam konteks gereja yang berfokus dari sejarah iman dan kaitannya dengan wacana sosial. Pada umumnya, praksis Pendidikan Kristiani di gereja masih bersifat indoktrinatif. Menyoroti hal itu, tulisan ini berupaya untuk mendialogkan teori pedagogi kritis (pembebasan) dari pemikiran Paulo Freire dengan Pendidikan Kristiani gereja (katekisasi sidi). Pembahasan dalam artikel ini menunjukkan bahwa penerapan konsep pedagogi kritis dari Paulo Freire dapat mengemansipasi pembelajaran katekisasi sebagai pengalaman iman religius. Bukti iman diperlihatkan dalam refleksi kehidupan personal dan dunia sekitarnya. Pendidikan Kristiani transformatif dalam pengajaran katekisasi penting dilakukan dengan aksi dan refleksi kritis sebagai penghayatan hidup bersama untuk perubahan sosial yang lebih baik.